In Situ Dielectric Al2O3/β‐Ga2O3 Interfaces Grown Using Metal–Organic Chemical Vapor Deposition. (28th August 2021) - Roy, Saurav; Chmielewski, Adrian E.; Bhattacharyya, Arkka; Ranga, Praneeth; Sun, Rujun; Scarpulla, Michael A.; Alem, Nasim; Krishnamoorthy, Sriram
Abstract: High quality dielectric‐semiconductor interfaces are critical for reliable high‐performance transistors. This paper reports the in situ metal–organic chemical vapor deposition of Al2 O3 on β‐Ga2 O3 as a potentially better alternative to the most commonly used atomic layer deposition (ALD). The growth of Al2 O3 is performed in the same reactor as Ga2 O3 using trimethylaluminum and O2 as precursors without breaking the vacuum at a growth temperature of 600 °C. The fast and slow near interface traps at the Al2 O3 /β‐Ga2 O3 interface are identified and quantified using stressed capacitance–voltage (CV) measurements on metal oxide semiconductor capacitor (MOSCAP) structures. The density of shallow and deep level initially filled traps (Dit ) are measured using ultraviolet‐assisted CV technique. The average Dit for the MOSCAP is determined to be 6.4 × 10 11 cm −2 eV −1 . The conduction band offset of the Al2 O3 / Ga2 O3 interface is also determined from CV measurements and found out to be 1.7 eV which is in close agreement with the existing literature reports of ALD Al2 O3 /Ga2 O3 interface. The current–voltage characteristics are also analyzed and the average breakdown field is extracted to be approximately 5.8 MV cm −1 . This in situ Al2 O3 dielectric on β‐Ga2 O3 with improved dielectric properties can enable Ga2 O3 ‐based high‐performance devices. Abstract : The growth of in situ Al2 O3 dielectric on β‐Ga2 O3 using metal organic chemical vapor deposition is reported. The vertical metal oxide semiconductor structures are characterized using transmission electron microscope imaging and electrical measurements to study structure/composition of the Al2 O3 layers, dielectric strengths and Al2 O3 /β‐Ga2 O3 interface properties. The results project the superiority of this technique compared to conventional atomic layer deposition technique.